Abnormal sensory gating in patients with different types of focal dystonias. Issue 12 (7th November 2018) - Conte, Antonella; Belvisi, Daniele; De Bartolo, Maria Ilenia; Manzo, Nicoletta; Cortese, Francesca Natalia; Tartaglia, Matteo; Ferrazzano, Gina; Fabbrini, Giovanni; Berardelli, Alfredo
ABSTRACT: Background: Movement execution in healthy individuals increases the somatosensory temporal discrimination threshold. These changes are a result of mechanisms of sensory gating at the subcortical level. Although the somatosensory temporal discrimination threshold is abnormally increased in patients with focal dystonias, the effect of movement execution on somatosensory temporal discrimination in dystonic patients is unknown. Objectives: The objective of this study was to determine whether somatosensory temporal discrimination threshold modulation induced by voluntary movement is normal in different forms of focal dystonia. Methods: We enrolled 71 dystonic patients (24 with blepharospasm, 31 with cervical dystonia, and 16 with focal hand dystonia) and 39 age‐matched healthy participants. Paired stimuli for the somatosensory temporal discrimination threshold were triggered by movement execution at movement onset and at various time intervals thereafter. We analyzed the kinematic features of the motor task to ascertain whether tactile input induces changes in movement parameters. Results: Movement execution led to greater and longer lasting increases in somatosensory temporal discrimination threshold values, both upon movement onset and at various time intervals thereafter, in patients with cervical dystonia and focal hand dystonia than in those with blepharospasm or the healthy participants. Somatosensory temporal discrimination testing did not induce any changes in the mean velocity of index finger movements in either patients or healthy participants. Conclusions: Somatosensory temporal discrimination threshold changes induced by movement execution are abnormal in focal dystonias. This abnormality is related to the type of dystonia. Abnormal gating of sensory information is likely involved in movement‐induced triggering or worsening of different forms focal dystonia. © 2018 International Parkinson and Movement Disorder Society